IMPLEMENTASI BLENDED LEARNING DALAM PEMBELAJARAN PAI DI MAN 4 PASAMAN BARAT PADA MASA COVID-19 - T Tasniwati (Profetika: Jurnal Studi Islam, 2021)
Madrasahs ranging from ibtidaiyah level to Aliyah have Islamic religious education curriculum, in accordance with the results of readings on various literature and initial observations made in MAN 4 West Pasaman islamic religious education learning is still faced with complex problems, the right logic for this is normal conditions are still difficult especially covid-19 conditions. The purpose of this research is to describe how blended learning is implemented in PAI learning during covid-19, this research method is descriptive qualitative, the data source used is the head of madrasah, deputy head, teacher of PAI field and some students selected purvosiv, to get data from informants used techniques that are prevalent in qualitative research namely observation, interview and documentation studies. The result of this study is, learning planning using blended learning there are differences in planning during and offline, the implementation of PAI learning with blended learning during covid-19 in MAN 4 Pasaman is done by dividing the learning ship based on odd weeks and odd classes. Third, evaluation of PAI learning with Blended learning is done by utilizing google form and video practice made by students.